Rare presentation of lateral meniscus tear with pathognomonic MRI finding. (2019) - Al Dosari, Mohamed; Elmhiregh, Aissam; Hammad, Mohamed; Alam, Sayed; Hameed, Shamsi
Highlights: Sport injury led to lateral meniscal posterior horn flap tear. This flap tear displaced posteriorly in our reported patient in the popliteus hiatus. This displaced tear appeared as double popliteus tendon in the sagittal MRI. The patient underwent arthroscopic partial meniscectomy and recovered very well in the later follow ups. Abstract: Introduction: Meniscal tears are common knee injuries that occur in different populations and particularly among athletes. Either isolated or accompanied with anterior cruciate ligament injury, meniscal tears can be a source of significant knee pain, locking and instability. Different patterns of meniscal tears are described radiologically and arthroscopically, however displacement of the torn part of the meniscus can cause characteristic appearance on MRI. Presentation of the case: The reported case is of a 27-year-old, previously healthy gentleman who presented to our care with acute sharp left knee pain and infrequent locking symptoms after playing football. The patient was limping and had lateral joint line tenderness along with positive McMurray's test for lateral meniscus. MRI study showed double popliteus tendon sign on the sagittal cuts. The patient was operated on elective list and underwent lateral meniscus posterior flap tear partial meniscectomy as the tear was in the white zone. On follow up after 4 months, the patient was satisfied and had regained full pre-injury functional capacity. Conclusion: Displaced lateral meniscus tear into the popliteal hiatus can be seen as a characteristic double popliteal sign in MRI as the displaced meniscus flap runs on the tibial surface parallel to the popliteus tendon.